Polemik Tindak Lanjut Rekomendasi Bawaslu dalam Perselisihan Hasil Pilkada di Mahkamah Konstitusi - Titis Anindyajati (Jurnal Adhyasta Pemilu, 2023)
In the context of the implementation and resolution of disputes related to the regional head elections (Pilkada) of 2020-2021, significant issues have emerged regarding the follow-up on recommendations given by the Election Supervisory Board (Bawaslu) to the General Election Commission (KPU). These issues primarily revolve around crucial questions about the division of authority between Bawaslu and KPU and have become a critical consideration in the petition submitted to the Constitutional Court (MK). The frequency of these questions highlights the existence of vital issues in the division of authority between Bawaslu and KPU. Given its position, the MK cannot avoid considering how the powers of Bawaslu and KPU are executed related to problems arising in the Pilkada process. This paper, employing normative legal research method and literature-based, analytically examines and reviews the authority position of KPU and Bawaslu as Pilkada organizers. Moreover, it observes the stance and response of the MK in resolving issues regarding the follow-up on recommendations proposed by Bawaslu. The study finds that the authority of KPU and Bawaslu in resolving administrative violations in Pilkada is proportional and mutually supervisory. Decisions issued by the KPU are based on Bawaslu's recommendations, and conversely, Bawaslu's recommendations act as a form of control over KPU before decisions are made. In deciding whether to implement Bawaslu's recommendations or not, the MK will make decisions on a case-by-case basis, based on the principle of utility, prioritizing legitimacy and integrity of the people's voice, ensuring that decisions are not rigidly or mechanistically applied.